Understanding visual literacy on teachers and students between Indonesia and Malaysia - Prameswari, Nadia Sigi; Cahyono, Agus; Subiyantoro, Slamet; Haryanto, Eko (Research Journal in Advanced Humanities, 2023)
Visual literacy is a very important skill in the 21st century. Visual literacy skill is part of the learning process for producing quality works of art. Building visual literacy competencies can provide long-term benefits in critical thinking skills. This study explored the ability to understand visual literacy in teachers and students in Indonesia and Malaysia. This study used qualitative research, and the respondents were lecturers and students of Universitas Negeri Semarang, Indonesia and Mara Technology University, Malaysia. The results indicated that Malaysian and Indonesian respondents did not know much about the images presented. The results of this study indicated that there were different perspectives on viewing and understanding visual literacy for teaching staff and students in Indonesia and Malaysia. The perspective of Indonesian respondents was more specific while explaining the answers to questions, whereas Malaysians tend to be less specific and general. The results also showed that each answer of each Indonesian respondent tends to be different from one another, while Malaysia tends to agree with other respondents. Dealing with the research is expected to make visual literacy learning methods suitable for education in Indonesia and Malaysia